Effects of extrusion and enzymatic debranching on the structural characteristics and digestibility of corn and potato starches. (June 2022) - Liu, Qing; Wang, Yihui; Yang, Yueyue; Bian, Shichao; Zhou, Xing; Zhu, Kunfu; Xu, Lulian; Jin, Zhengyu; Jiao, Aiquan
Abstract: Amylose content has a profound impact on the contents of slowly digestible starch and resistant starch. Enzymatic debranching is a safe method to increase the amylose content, however, the lower substrate concentration and high viscosity of fully gelatinized starch limit the efficiency and yield of this method. This paper aims to explore the effects of extrusion and enzymatic debranching on increasing the amylose content thereby increasing slowly digestible starch and resistant starch contents. Different starch concentrations (10%, 15%, and 20%) of extruded corn starch (ECS) and extruded potato starch (EPS) were used to debranch. Both debranched ECS and debranched EPS showed high amylose content of approximately 90%, indicating that all samples with different starch concentrations achieved high-efficiency enzymatic debranching. The high-performance liquid chromatograph results indicated that the samples were mainly short amylose. The samples exhibit a typical B-type crystalline structure and the relative crystallinity of them exceeds 37%. The short amylose exhibited rapid rearrangement ability, with the gelatinization temperature range of rescanning determined as 80–125 °C, this will facilitate the formation of slowly digestible starch and resistant starch. The slowly digestible starch and resistant starch contents of the samples (debranched ECS and debranched EPS) were between 23% and 30% and between 31% and 37%, respectively. These results indicate that the extrusion and enzymatic debranching of a high substrate concentration can efficiently increase the amylose content, thereby significantly reducing the digestibility of starch, and has broad prospects of the actual production of slowly digestible starch and resistant starch. Graphical abstract: Image 1